Pemodelan Hubungan Antara Accessibility, Perceived Price, Facilities, Visitor Satisfaction, Dan Revisit Intention : Studi Kasus Taman Safari Cisarua Bogor - Hanifah Ananda Putri; Usep Suhud; Meta Bara Berutu (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
The purpose of this research is to examine several hypotheses regarding the relationships between accessibility, perceived price, facilities, visitor satisfaction, and revisit intention at Taman Safari Cisarua Bogor. This study involved 203 respondents residing in the Jakarta, Bogor, Depok, Tangerang, and Bekasi areas, with the requirement that respondents be at least 18 years old and have visited Taman Safari Cisarua Bogor at least once in the past three years. Data collection was conducted through surveys using questionnaires, and the data were analyzed using SPSS and Amos software. The results of the study indicate that perceived price and facilities have a positive and significant effect on visitor satisfaction. Additionally, accessibility and visitor satisfaction also have a positive and significant effect on revisit intention. However, the study found that accessibility does not have a positive and significant effect on visitor satisfaction, and facilities do not have a positive and significant effect on revisit intention.